Mexican species of Exetastes (Hymenoptera: Ichneumonidae: Banchinae), with description of three new species - Andrey I. Khalaim; Enrique Ruiz-Cancino (Revista Mexicana de Biodiversidad)
Twenty one species and subspecies of Exetastes Grav. are recorded from Mexico. Exetastes arteagus sp. nov., E. gauldi sp. nov. and E. lascivus sp. nov. are described as new. Exetastes pasculus Gauld et Ugalde is recorded for the first time for Mexico. New data on distribution in Mexico and a key to the Mexican species of Exetastes are provided. The known Mexican fauna is closer to the Nearctic fauna than to the Costa Rican fauna: 13 out of 21 Mexican species and subspecies (62%) also occur in the USA and Canada, 4 species (19%) also occur in Costa Rica, and 3 species and 1 subspecies (19%) are known from Mexico only. The most abundant species of the genus in Mexico is E. tarsalis.